Violence and stress perceived by first year medical students in a public university, 2016 - Amemiya, Isabel (2019)
Introduction. Violence in medical school is a frequent phenomenon but little studied in students of the first cycles. Objective. To determine the perception of bullying and stress by students of the 1st year of medicine of the Universidad Nacional Mayor de San Marcos (UNMSM), 2016. Methods. Descriptive cross - sectional study carried out in 133/160 (83%) students enrolled in 1st year of medicine school at UNMSM. A validated instrument was used. Results. The students perceived some type of violence in 95,5% (127 students), like verbal aggression in 91%, social exclusion 84,2%, physical 58,6%, bullying 84,2% and, malicious sexual conduct and harassment in 41,4%. The stress was reported in 94% of students, usually due to the demands of the studies, followed by family problems. Conclusions. The perception of violence and stress by first year students of medicine school was high, the most frequent cause were the verbal aggression, social exclusion and bullying.